Análisis sobre los procesos de auditoría en la Empresa Comercial ABC con la inteligencia artificial - Gortaire Encalada, Carlos Luis (2024)
This research report addresses the audit processes in the commercial company ABC using artificial intelligence to enhance efficiency and accuracy. Critical areas in the audit processes were identified through questionnaires directed at employees from various departments. The results showed that the implementation of advanced technologies is positively correlated with job satisfaction and organizational efficiency. The research highlights the need for continuous training and investment in artificial intelligence tools to optimize audits. It is recommended to develop a comprehensive employee welfare program to improve satisfaction and retention. The methodology used included a mixed qualitative and quantitative approach, with a descriptive study employing data collection techniques such as questionnaires and document analysis. The findings emphasize the importance of modernizing administrative and audit processes to ensure more effective and accurate corporate management. The report concludes with practical recommendations for the implementation of AI and training strategies, aimed at addressing the identified issues and enhancing efficiency and satisfaction within the organization.